PEMBELAJARAN MATEMATIKA BERBASIS ETNOMATEMATIKA DALAM MENINGKATKAN PEMAHAMAN MATEMATIS DAN KARAKTER SISWA DI SEKOLAH DASAR - Rahman, Sidiq Aulia; Hermawan, Ludi; Ghiffany, Regina Kaysa (Universitas Islam Nusantara, 2025)
This study aims to examine the effectiveness of ethnomathematics-based mathematics learning in enhancing mathematical understanding and character development among elementary school students. The ethnomathematics approach integrates local culture into mathematics instruction, making the material more contextual and meaningful for students. The research was conducted at SDN 184 Kota Bandung, with the population consisting of all fifth-grade students and a sample of two classes totaling 60 students. A quasi-experimental method was employed, using a pretest-posttest control group design. Data were collected through mathematical comprehension tests and character questionnaires, then analyzed using statistical tests (t-tests) to determine significant differences between the experimental and control groups. The findings indicate that ethnomathematics-based learning improves mathematical understanding and fosters character values such as creativity, cooperation, and cultural appreciation in students. The implications of this study can serve as a reference for educators in developing more innovative and character-driven mathematics instruction.